2017
DOI: 10.11648/j.jctr.20170501.11
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hesperetin in the Management of Diabetes Mellitus and Its Complications

Abstract: Diabetes mellitus is a chronic metabolic disease which is a serious global problem. Many antidiabetic therapies focus on improving insulin sensitivity, increasing insulin production, and/or decreasing the level of blood glucose. Hesperetin is a flavanoid commonly found in many herbal medicines and food. Hesperetin seem to demonstrate adequate properties. Animal studies were carried out for 45days and at the end of 45 th day blood samples were collected and various biochemical parameters were measured using aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…DM is a complex metabolic condition characterized by chronic hyperglycemia and disruptions in carbohydrate, lipid, and protein metabolism caused by flaws in insulin secretion, action, or both [ 29 ]. It is one of the most common metabolic illnesses and is regarded as one of the primary causes of death worldwide [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…DM is a complex metabolic condition characterized by chronic hyperglycemia and disruptions in carbohydrate, lipid, and protein metabolism caused by flaws in insulin secretion, action, or both [ 29 ]. It is one of the most common metabolic illnesses and is regarded as one of the primary causes of death worldwide [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various methods were used to evaluate the anti-diabetic potential of hesperetin ( Fig. 10 ) [ 103 , 104 , [204] , [205] , [206] , [207] ]. Hesperetin has demonstrated its ability to improve glucose homeostasis in animal models of diabetes.…”
Section: In Vivo and In Vitro Anti-diabet...mentioning
confidence: 99%
“…Hesperetin has demonstrated its ability to improve glucose homeostasis in animal models of diabetes. Studies have shown that hesperetin treatment resulted in improvements in glucose levels, insulin levels, glycogen levels, and glucose metabolic enzymes, while also reducing insulin resistance [ [205] , [206] , [207] ]. Additionally, hesperetin normalized the activities of glucose-regulating enzymes and reduced serum and liver lipid levels, thereby improving glucose metabolism in vivo [ 204 ].…”
Section: In Vivo and In Vitro Anti-diabet...mentioning
confidence: 99%
“…Male albino Wistar rats -Reduction in glucose plasma and increase in insulin levels similar to glibenclamide -Recuperation of pancreatic β-cells -Improvement in glucokinase activity and glucose-6-phosphate dehydrogenase -Inhibition of hepatic gluconeogenesis-decrease in the level of gluconeogenic enzymes-glucose-6-phosphatase and fructose-1,6-bisphosphatase -Increased glycogen content in hepatocytes -Antioxidant-increase in activity of enzymic antioxidants -Anti-hyperlipidemic effect-enhanced insulin secretion, which led to a reduction in cholesterol synthesis and due to the ability of hesperetin to bind bile acids, which resulted in a decrease in the cholesterol absorption -Protective effect on hepatic damage -Renoprotective effect [152] Wistar rats -Attenuation of gluconeogenesis by inhibition of mitochondrial pyruvate carrier, uncoupling of mitochondrial oxidative phosphorylation, inhibition of mitochondrial respiratory chain at Complex I, and deviation of NADH supply for gluconeogenesis and mitochondria due to a prooxidant action, deviation of glucose 6-phosphate for glucuronidation reactions [153] Adult male Wistar albino rats -Reduction of plasma glucose because of the increased release of insulin from the existing β-cells and/or regenerated β-cells of the pancreas, restored insulin sensitivity or inhibition of intestinal absorption of glucose, or enhanced the utilization of glucose by peripheral tissues -Improved lipid profile -Improved pancreatic islets' morphology [154] Male mice -Anti-hyperglycemic-increased insulin production and reduced blood glucose levels [155] Wistar rats -Anti-hyperglycemic-decrease in glucose levels -Antioxidant-increase in antioxidant enzymes-SOD, CAT, GSH, GPx activity -Anti-inflammatory-decrease in pro-inflammatory cytokines levels-TNF-α, IL-17 -Anti-apoptotic-suppression of caspase-3 and maintenance of mitochondrial membrane potential [156] In vitro In silico -α-glucosidase inhibition [157] In vitro In silico -Dipeptidyl peptidase-4 inhibition [143] HepG2 cells -Increase in protein level and direct activation of SIRT1, which was accompanied by induction of AMPK phosphorylation [158] RAW264.7 cells -Inhibitory effect on oxidative stress and inflammation induced by AGEs [159] Male Sprague Dawley rats -Up-regulation and Increased Glo-1 enzymatic activity -Anti-inflammatory-decreased level of pro-inflammatory cytokines (IL-1β, TNF-α) -Enhancement of Nrf2/ARE pathway [160] The Importance of Hesperidin and Hesperetin Modes of Action in DM Oxidative stress is a major factor contributing to DM pathogenesis. It affects two mechanisms, which are improperly working in this condition-insulin secretion and insulin action [161,162].…”
Section: Hesperidin Hesperetinmentioning
confidence: 99%